2015
DOI: 10.1037/a0038929
|View full text |Cite
|
Sign up to set email alerts
|

Understanding the psychology of bullying: Moving toward a social-ecological diathesis–stress model.

Abstract: With growing recognition that bullying is a complex phenomenon, influenced by multiple factors, research findings to date have been understood within a social-ecological framework. Consistent with this model, we review research on the known correlates and contributing factors in bullying/victimization within the individual, family, peer group, school and community. Recognizing the fluid and dynamic nature of involvement in bullying, we then expand on this model and consider research on the consequences of bull… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
285
0
54

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 483 publications
(376 citation statements)
references
References 143 publications
8
285
0
54
Order By: Relevance
“…For these youth, there seems little optimism for change. Research over the past few decades has documented links between victimization and a host of negative mental health, social, and academic outcomes (see Card, Isaacs, & Hodges, 2007;Hawker & Boulton, 2000;Swearer, Espelage, et al, 2010;Swearer & Hymel, 2015, for reviews), with increasing evidence that victimization can "get under the skin," impacting neurobiological functioning (see Vaillancourt, Hymel, & McDougall, 2013). As part of this special issue, McDougall and Vaillancourt (2015) move beyond one-time, snapshot correlates to provide a critical analysis of research on the longitudinal impact of peer victimization over the years of childhood and adolescence, with a focus on how peer victimization during the school years plays out for adjustment in adulthood.…”
Section: How Stable Is Peer Victimization?mentioning
confidence: 99%
“…For these youth, there seems little optimism for change. Research over the past few decades has documented links between victimization and a host of negative mental health, social, and academic outcomes (see Card, Isaacs, & Hodges, 2007;Hawker & Boulton, 2000;Swearer, Espelage, et al, 2010;Swearer & Hymel, 2015, for reviews), with increasing evidence that victimization can "get under the skin," impacting neurobiological functioning (see Vaillancourt, Hymel, & McDougall, 2013). As part of this special issue, McDougall and Vaillancourt (2015) move beyond one-time, snapshot correlates to provide a critical analysis of research on the longitudinal impact of peer victimization over the years of childhood and adolescence, with a focus on how peer victimization during the school years plays out for adjustment in adulthood.…”
Section: How Stable Is Peer Victimization?mentioning
confidence: 99%
“…Vulnerability-stress theory asserts that the development of internalizing and externalizing behavior problem is as a result of the combination of predisposing individual cognitive vulnerabilities and environmental hardships, stressors, or adversities (Lazarus, 1993). One's experience of adverse life events and perceptions about those events contributes to psychopathology (Swearer and Hymel, 2015). Various studies have found support for vulnerability-stress theory in understanding adolescent stress and depressive symptoms (Hankin, 2008;Hankin et al, 2015;Paredes and Zumalde, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…This can make them susceptible to moral disengagement (being convinced that certain ethical standards don't apply to them in particular contexts) and to minimizing responsibility for their behaviour. 17 Furthermore, increasing levels of depression, anxiety, self-injury and substance use disorders throughout adolescence are testament to their vulnerability. [18][19][20] These individual vulnerabilities can make peer relations stressful, particularly among female adolescents who are more susceptible to interpersonal stress compared to males.…”
Section: Impact Of Cyberbullying Victimization On Mental Health and Smentioning
confidence: 99%
“…Based on these findings, governments are urged to denounce the practice of CV, to develop legislation and programs that will reduce the opportunities for individuals to perpetrate CV, and to create effective strategies for intervening when CV occurs. Recommended are multicomponent schoolwide programs based on the SocialEcological Diathesis-Stress Model, 17 which emphasizes the dynamic and fluid nature of bullying across the individual, family, peer group, school and community contexts. [30][31][32] For instance, the Cyber Friendly Schools Program 33,34 is an online whole-school cyberbullying prevention and intervention program built on a social-ecological approach; it reported a significant decline in CV perpetration at one year in a group randomized controlled trial.…”
Section: Cyberbullying and Health Outcomesmentioning
confidence: 99%